Tragetória da educação básica à educação superior no curso de pedagogia e a experiência no Pacto Nacional Pela Alfabetização Na Idade Certa (PNAIC) - SILVA, Leni Gomes da (2020)
This Memorial is a Course Conclusion Paper, and the account of my formation trajectory from Basic Education to Higher and Professional Education, narrating the experience in the Right Age Literacy Program / PNAIC. The objective was to analyze my academic and professional career. The methodology used was the academic memorial that seeks in memory the regatta of a time of formation and work, subsidized by a bibliography. I conclude that the experience as a student and teacher, allowed me to broaden the perspectives on the initial and continued formation. mine, as well as the teachers I coordinated at PNAIC, leading me to understand that my academic and professional career complemented each other in theory and practice, that the experience as coordinator and trainer was remarkable in the continuing education of teachers, where the challenges of a quality education are always present.